The Role of Social Media Entrepreneurship as a Mediation on the Influence of Job Crafting on Workforce Agility - Ryani Dhyan Parashakti; Muhamad Ekhsan (PT Mattawang Mediatama Solution, 2024)
This study aims to analyze the effect of job crafting on workforce agility with enterprise social media as a mediating variable among company employees in Bekasi. With increasing job demands and rapid changes in the business environment due to the industrial revolution 4.0 and the COVID-19 pandemic, good workforce agility is needed so that employees can adapt to these changes. Job crafting allows employees to customize their jobs according to their abilities and needs, while enterprise social media is expected to facilitate communication and collaboration to increase agility. This research uses a survey method by distributing questionnaires to 65 respondents of company employees in Bekasi. Data were analyzed with Structural Equation Modeling. The results showed that job crafting has a significant positive effect on workforce agility and enterprise social media, but enterprise social media has no significant effect on workforce agility and is unable to mediate the relationship between job crafting and workforce agility.